Before anticipation - Jackson, ML (RMIT University, 2012)
The possibility of any recognition of 'access' as such would be constituted in the future anterior, what I would retrospectively encounter, or encounter again, as that which marks or constitutes a threshold or opening. The temporality of 'access' may be understood via terms we encounter in phenomenology's understanding of 'presencing': anticipation and recollection, or 'thrownness' and 'futurity'. We may consider the notion of 'journal' as an inscribing-presencing, as that which accounts for the 'day' as such, a temporalising of accessability according to the peculiar notion that every encounter is necessarily a reencounter, whose 'time' is that of a future anterior. This paper engages these notions in order to question the journal, and the phenomenon of access, in terms of what grounds an ethics of the future anterior and what constitutes the movement from ethics to politics in journal practices. Key to this discussion will be two texts by Jacques Derrida from Acts of Literature: Before the Law, in Derrida's discussion of Kafka's understanding of the law of the 'gate', and The Law of Genres, particularly Derrida's discussion of Maurice Blanchot's Madness of the Day.
Keywords: Temporality; Phenomenology; Derrida; Blanchot; Ethics